Impacts of Cow Dung and Poultry Manure on the Mineral Nutrient Uptake of Red Amaranth Grown in a Mixture Of Acid and Calcareous Soils (Dhaka University Journal of Biological Sciences, 2023)
A pot experiment was performed in the net house to observe the influence of cow dung and poultry manure on the growth of red amaranth grown in the amended soil (mixture of acid and calcareous soil). Acid soil was mixed with calcareous soil at a ratio of 3:1 for experiment with red amaranth. The pot experiment was conducted with the mixed soil indicated by T0M (control-where no amendment was added), three different rates of cow dung such as T1 (3 ton/ha), T2 (6 ton/ha) and T3 (9 ton/ha) and three rate of poultry manure designated as T4 (2 ton/ha), T5 (4 ton/ha) and T6 (6 ton/ha). Treatment responses were evaluated in terms of different parameters including uptake of nutrients by plants and post-harvest properties of soil such as physico-chemical properties and residual nutrient content of the soil. It is evident from the experiment that the uptake of the plant nutrients was the best in the mixed soil (T0M-control) than those of the acid (TA) and calcareous soils (TC). On the other hand, T3 (9 ton cow dung/ha) showed the highest uptake of nutrients except for S and Mg among the all treatments. In the post-harvest soil, the maximum nutrient contents increased in the highest doses of cow dung (except for the S, Cu, Mn and Zn) and poultry manure (except for the K, Ca, Mg and Fe) treatments. Results of the study showed that soil amendment (mixture of acid and calcareous soil) can be a suitable reclamation process while the addition of organic manures can also improve soil health.Dhaka Univ. J. Biol. Sci. 31(2): 329-342, 2022 (July)